Evaluation of green and circular products' features on the consumers' purchase intention towards remanufactured electronic products in Florianópolis-SC - Kerber, Jaqueline Carneiro (2021)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Produção, Florianópolis, 2021.